Life quality related to health in asthmatic children and their caretaker. - Rafael Alejandro Gómez Baute; Yaney Gonzalez Iglesias; Juana María Morejón Fernández; Roberto Travieso Peña (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Fundament: In present days it is known that sanitary assistance should not only be focused on patient's survival (life quantity), but also in the life quality. Objective: to evaluate health-related life quality in children with asthma and their caretakers through 4 measurement devices. Methods: Analytic-prospective-descriptive study to evaluate life quality of children and their caretakers. There was a universe of 72 asthmatic children from the number 32, 37, and 49 clinics of Palmira. For life quality estimation three questionnaires were used. We calculated the standard deviation and measure of the variables. The variations in measurement were evaluated through minimum change difference. Three measurements were realized in one month interval. Results: The 61.8% of patients evaluated with the American college quality test had bad life quality. The evaluation of life quality using the questionnaire of the Mc Master the Juniper University threw a moderate life quality, being the emotive sphere the most affected. The evaluation of life quality in caretakers showed a deterioration.